Effect of different initial C/N ratio of cow manure and straw on microbial quality of compost - M. A. Macias-Corral; J. A. Cueto-Wong; J. Morán-MartÃnez (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose The effect of different initial carbon to nitrogen (C/N) ratios on the prevalence of Salmonella spp., fecal coliforms and helminth eggs over composts produced from several mixtures of maize straw (S) and dairy manure (M) was investigated. Method Four C/N ratios (21, 22, 27, and 38) were evaluated, including one with manure only (C/N 21). The composting process was performed under field conditions in northern Mexico. Results The process lasted 51 days; Salmonella spp. was reduced 1â2 log (>â94%) in most treatments, except for the C/N ratio of 27 which achievedâ<â1 log reduction (about 35%). Fecal coliforms elimination was 3â4 log (>â99%) in all treatments while helminth eggs achievedâ<â1 log (72â87%, depending on treatment). In this study, the mixture with initial C/N ratio of 22 (25% Sâ+â75% M), which had the lowest amount of straw, resulted in the highest elimination of Salmonella spp., fecal coliforms, and helminth eggs. This mix complied with current Mexican sanitary regulations for compost use. The composts produced from the other C/N ratios complied only with the limits for one or two of the microorganisms that were analyzed. Conclusion The initial C/N ratios in compost from straw and manure influences microbial reduction. The final C/N of the mixes ranged from 14 to 16, indicative of stable compost. Compared to fecal coliforms, Salmonella spp. and helminth eggs were more resilient.